The Context of the Teaching Methods of Full Communicative Competence in English of the 11th Grade Teachers of the Middle Technical - Vocational Institutes in the Province of Cabinda (Angola) - Joao, Armando; Sanchez, Francisco Raso (European Scientific Journal, ESJ, 2017)
The objective of this article is to analyse the context of teaching methods of English as a foreign language of English teachers of 11th grade of the Middle Technical - Vocational Institutes of Cabinda (Angola). This work consists of understanding why students do not learn full communicative competence in English, the reasons why students study this subject for two years in tenth and eleventh grade at school and three years in seventh to ninth grade but do not speak, do not read and can’t even understand a simple request. They finish their studies without acquiring necessary linguistic competence in English. However, it is known that the role of the teacher is to guide the students to build their knowledge to orient their social lives. The results of the research show that teachers mostly use grammar translation methods, and they don’t use other pedagogical resources such as publicity posters which would help students to acquire the necessary linguistic communicative competences.